2014
DOI: 10.2355/isijinternational.54.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slag Properties on Mixing Phenomena in Gas-stirred Ladles by Physical Modeling

Abstract: The effect of slag properties (thickness and viscosity), have been evaluated in terms of mixing time, exposed surface or ladle eye and energy dissipation. A nozzle configuration defined in terms of the number of nozzles, its radial position and gas flow rate has been employed to describe the influence of the top layer on mixing phenomena. It has been found a negative effect of both slag thickness and slag viscosity on mixing time, on the other hand, the same properties are useful to decrease the exposed surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…Recently, Chen et al 21) studied the effect of salt tracer amount on the mixing time, which proposes that the tracer selection should be considered combined with the criterion of the definition of mixing. In addition, Conejo et al 22,23) reported the effects of slag properties (thickness and viscosity) and nozzle diameter on mixing phenomena in gas-stirred ladles by physical modeling, a negative effect of both slag thickness and slag viscosity on mixing time was found, and an increase in nozzle diameter decreases mixing time, but the effect is not significant. However, relatively little work has been reported on the effect of slag eye formation on the mixing time in ladle metallurgy.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…Recently, Chen et al 21) studied the effect of salt tracer amount on the mixing time, which proposes that the tracer selection should be considered combined with the criterion of the definition of mixing. In addition, Conejo et al 22,23) reported the effects of slag properties (thickness and viscosity) and nozzle diameter on mixing phenomena in gas-stirred ladles by physical modeling, a negative effect of both slag thickness and slag viscosity on mixing time was found, and an increase in nozzle diameter decreases mixing time, but the effect is not significant. However, relatively little work has been reported on the effect of slag eye formation on the mixing time in ladle metallurgy.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…In 2011, Y. S. Chen et al 9) studied the effect of the number and positions of plugs on mixing time, suggesting that the shortest mixing time could be obtained when the plug at 0.7R from the center of ladle bottom with only one plug, whereas at 0.5-0.7R with 60-90 degree when two plugs. In a recent study, Amaro-Villeda et al 14) found the shortest mixing time was at the position 0.5R with only one plug, compared with all other cases including two plugs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for high-capacity ladles used in many steel factories of China, two porous plugs are usually utilized, and their positions and relative angle have effect on the homogenization of molten steel. 1,6) For the function of argon gas in ladle refining, many studies were performed in the earlier years through water model 1,2,4,6) and mathematical simulation 5,[7][8][9] from different aspects such as (a) gas injection and transport, [10][11][12][13] (b) the effect of top slag layer, [14][15][16][17][18][19] (c) stirring and mixing. [20][21][22][23][24][25][26][27][28] In 1975, Nakanishi et al 10) investigated the correlation between gas mixing efficiency and mass transfer in a model ladle and explained this correlation with turbulence theory.…”
Section: Introductionmentioning
confidence: 99%
“…Amaro-Villeda [69] applied Mazumdar's model to study the mixing time in a model of steel ladles with different bottom nozzle configurations. Under the system of multiple injection ladles, the mixing phenomena was getting complicated.…”
Section: Mixing Time and Stirring Energy Investigation In Multiphase mentioning
confidence: 99%
“…Many studies correlated measured mixing time against experimental variables such as bath level, container dimension, flowrate, and nozzle configuration, and proposed empirical or semi-empirical equations to predict mixing. However, only a few studies took the overlying slag layer into consideration [54][55][56][57][58][59][60][61][62][63] .…”
Section: Mixing Time and Stirring Energy Investigation In Multiphase mentioning
confidence: 99%